Reconstruction of the Vancomycin-Susceptible Staphylococcus aureus Phenotype From a Vancomycin-Intermediate S. aureus XN108 - Peng, Huagang; Rao, Yifan; Yuan, Wenchang; Zheng, Ying; Shang, Weilong; Hu, Zhen; Yang, Yi; Tan, Li; Xiong, Kun; Li, Shu; Zhu, Junmin; Hu, Xiaomei; et al. (Frontiers in Microbiology, 2018)
The emergence of vancomycin-intermediate Staphylococcus aureus (VISA) has raised healthcare concerns worldwide. VISA is often associated with multiple genetic changes. However, the relative contributions of these changes to VISA phenotypes are incompletely defined. We have characterized VISA XN108 with vancomycin MIC of 12 μg/ml. Genome comparison revealed that WalK(S221P), GraS(T136I), and RpoB(H481N) mutations possibly contributed to the VISA phenotype of XN108. In this study, the above mutations were stepwise cured, and the phenotypes between XN108 and its derivates were compared. We constructed four isogenic mutant strains, XN108-WalK(P221S) (termed as K65), XN108-GraS(I136T) (termed as S65), XN108-RpoB(N481H) (termed as B65), and XN108-WalK(P221S)/GraS(I136T) (termed as KS65), using the allelic replacement experiments with the native alleles derived from a vancomycin-susceptible S. aureus isolate DP65. Antimicrobial susceptibility test revealed K65 and S65 exhibited decreased vancomycin resistance, whereas B65 revealed negligibly differed when compared with the wild-type XN108. Sequentially introducing WalK(P221S) and GraS(I136T) completely converted XN108 into a VSSA phenotype. Transmission electronic microscopy and autolysis determination demonstrated that cell wall thickening and decreasing autolysis were associated with the change of vancomycin resistance levels. Compared with XN108, K65 exhibited 577 differentially expressed genes (DEGs), whereas KS65 presented 555 DEGs. Of those DEGs, 390 were common in K65 and KS65, including those upregulated genes responsible for citrate cycle and bacterial autolysis, and the downregulated genes involved in peptidoglycan biosynthesis and teichoic acid modification. In conclusion, a VSSA phenotype could be completely reconstituted from a VISA strain XN108. WalK(S221P) and GraS(T136I) mutations may work synergistically in conferring vancomycin resistance in XN108.